# 2log*m=Log*36

## Simple and best practice solution for 2log*m=Log*36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2log*m=Log*36 equation:

Simplifying
2log * m = Log * 36
Multiply glo * m
2glmo = Log * 36
Reorder the terms for easier multiplication:
2glmo = 36goL
Solving
2glmo = 36goL
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '-36goL' to each side of the equation.
2glmo + -36goL = 36goL + -36goL
Combine like terms: 36goL + -36goL = 0
2glmo + -36goL = 0
Factor out the Greatest Common Factor (GCF), '2go'.
2go(lm + -18L) = 0
Ignore the factor 2.
Subproblem 1Set the factor 'go' equal to zero and attempt to solve:
Simplifying
go = 0
Solving
go = 0
Move all terms containing g to the left, all other terms to the right.
Simplifying
go = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(lm + -18L)' equal to zero and attempt to solve:
Simplifying
lm + -18L = 0
Reorder the terms:
-18L + lm = 0
Solving
-18L + lm = 0
Move all terms containing g to the left, all other terms to the right.
Add '18L' to each side of the equation.
-18L + 18L + lm = 0 + 18L
Combine like terms: -18L + 18L = 0
0 + lm = 0 + 18L
lm = 0 + 18L
Remove the zero:
lm = 18L
Add '-1lm' to each side of the equation.
lm + -1lm = 18L + -1lm
Combine like terms: lm + -1lm = 0
0 = 18L + -1lm
Simplifying
0 = 18L + -1lm
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`